Teachers' understanding and practice towards thematic approach in teaching integrated living skills (ILS) in Malaysia - Kon, Chon Min; Mat Rashid, Abdullah; Nazri, Mohd Ibrahim (Center for Promoting Ideas, 2012)
Thematic approach is one of the teaching strategy that uses themes towards creating an active, interesting and meaningful learning. The purpose of this research is to identify the teachers’ understanding and practice towards thematic approach in teaching Integrated Living Skills (ILS). A total of 132 Integrated Living Skills teachers were involved in this study. This research was conducted in the District of Kinta Utara, Perak, Malaysia and the instruments used were questionnaires. The finding indicated that the Integrated Living Skills teachers’ understanding level towards thematic approach is high. Findings also showed that ILS teacher were often using thematic approach in teaching Integrated Living Skills. There is a significant relationship between teachers’ understanding level towards thematic approach with teachers’ constant practice. The findings also shows teachers’ years of experience in teaching were not significantly different from their practices on thematic approach.